2012
DOI: 10.1089/jamp.2011.0916
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Deposition in Health and Disease

Abstract: The success of inhalation therapy is not only dependent upon the pharmacology of the drugs being inhaled but also upon the site and extent of deposition in the respiratory tract. This article reviews the main mechanisms affecting the transport and deposition of inhaled aerosol in the human lung. Aerosol deposition in both the healthy and diseased lung is described mainly based on the results of human studies using nonimaging techniques. This is followed by a discussion of the effect of flow regime on aerosol d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
273
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(281 citation statements)
references
References 46 publications
5
273
0
3
Order By: Relevance
“…The changes in MMAD with the Acapella Choice and Acapella Duet (4.32 m to ϳ 1.23 m) are likely to alter the site of intrapulmonary deposition. 5,11 In addition, there was a significant reduction in the dose captured by the cascade impactor (from 65% to 69%). Impaction loss within the PEP device is the most likely mechanism for that decrease: this was confirmed by the analysis of the washings from the PEP devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in MMAD with the Acapella Choice and Acapella Duet (4.32 m to ϳ 1.23 m) are likely to alter the site of intrapulmonary deposition. 5,11 In addition, there was a significant reduction in the dose captured by the cascade impactor (from 65% to 69%). Impaction loss within the PEP device is the most likely mechanism for that decrease: this was confirmed by the analysis of the washings from the PEP devices.…”
Section: Discussionmentioning
confidence: 99%
“…4 Particle size is an important factor in determining intrapulmonary deposition of inhaled aerosols. 5 Laube et al reported a decrease in intrapulmonary deposition and a slightly more peripheral aerosol distribution when a breath-enhanced nebulizer was coupled to a PEP device. 6 Dornelas de Andrade et al reported a decrease in intrapulmonary deposition when a vibratory PEP device was coupled to a nebulizer.…”
Section: Introductionmentioning
confidence: 99%
“…Smaller particles (Ͻ 2 m) deposit mainly in the alveolar region and are probably the most apt to act systemically, whereas particles of intermediate size (2-6 m) are best suited to treat the central and small airways. 34 Hence, even if the ultrasonic nebulizer gave the largest particle size, all 3 types of nebulizers proved satisfactory according to this criterion. Sangwan et al 35 compared 2 jet nebulizers and found respirable fractions of 6% and 14%.…”
Section: Particle Size Distribution and Respirable Fractionmentioning
confidence: 93%
“…46,47 More and more studies have demonstrated that the dosage at the diseased site, rather than the total dose, should be used as the predictor of clinical outcomes. 48 In addition, the initial site of drug deposition has an important effect on its bioavailability and associated therapeutic effectiveness. 49 Another advantage of the newly proposed delivery system is its versatility.…”
Section: Discussionmentioning
confidence: 99%